Earthworms change the quantity and composition of dissolved organic carbon and reduce greenhouse gas emissions during composting. (April 2017) - Nigussie, Abebe; Bruun, Sander; de Neergaard, Andreas; Kuyper, Thomas W.
Highlights: Earthworms modified the quantity and composition of dissolved organic carbon. A higher (supra-optimal) feeding ratio reduced the stabilisation process. A higher feeding ratio increased N2 O emissions. The hydrophilic-to-hydrophobic ratio could be used to assess compost stability. Abstract: Dissolved organic carbon (DOC) has recently been proposed as an indicator of compost stability. We assessed the earthworms' effect on DOC content and composition during composting, and linked compost stability to greenhouse gas emissions and feeding ratio. Earthworms reduced total DOC content, indicating larger stability of vermicompost than of thermophilic compost. The concentrations of humic acid and fulvic acid were reduced by earthworms, whereas there was no significant effect on hydrophobic neutrals and hydrophilics. The humic acid fraction was depleted more quickly than the other compounds, indicating humic acid degradation during composting. The optimum feeding ratio decreased DOC content compared to the high feeding ratio. The lowest N2 O emissions were also observed at the optimum feeding ratio. Our study confirmed the use of DOC content and composition as an indicator of compost stability and suggested that feeding ratio should be considered when assessing the earthworms' effect on stabilisation and greenhouse gas emissions.